Does the internet increase the job finding rate? Evidence from a period of internet expansion - Manuel Denzer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We examine the impact of household access to the internet on job finding rates in Germany during a period (2006_2009) in which internet access increased rapidly, and job-seekers in-creased their use of the internet as a search tool. During this period, household access to the internet was almost completely dependent on connection to a particular technology (DSL). We therefore exploit the variation in connection rates across municipalities as an instrument for household access to the internet. OLS estimates which control for differences in individual and local area characteristics suggest a job-finding advantage of about five percentage points. The IV estimates are substantially larger, but much less precisely estimated. However, we cannot reject the hypothesis that, conditional on observables, residential computer access with internt was as good as randomly assigned with respect to the job-finding rate. The hypothesis that residential computer access with internet helped job-seekers find work because of its affect on the job search process is supported by the finding that residential internet access greatly increased the use of the internet as a search method. We find some evidence that computer access reduced the use of traditional job search methods, but this effect is outweighed by the increase in internet-based search methods.
Keywords: J64; L86; R23; J64; C26; L86; 330; Job search; unemployment; job finding rate; internet; DSL